Regional Drought Analysis with Standardized Precipitation Evapotranspiration Index (SPEI): Gediz Basin, Turkey - Mustafa Öney; Alper Anlı (Journal of Agricultural Sciences)
In this study, regional drought analysis was performed with the Standard Precipitation Evapotranspiration Index (SPEI) and L-moment techniques by using the monthly average temperature and monthly total rainfall amounts collected from five sites in the Gediz basin in Turkey. Using the monthly average temperatures, the Potential Evapotranspiration (PET) amounts obtained by the Thornthwaite method and the monthly total rainfall amounts were divided into 5 different reference periods as 1, 3, 6, 9 and 12 months. Expressing the difference between rainfall and potential evapotranspiration amounts, the water balance (Di) series showed that almost all of the 9 and 12-month periods suffered from water deficiency and the 3-month period was water excessive. After determining the distributions that provide the best adaptation to the water balance series, according to the SPEI values obtained, near-normal conditions prevailed in all sites, while moderate and severe arid and humid conditions sometimes occurred, while extremely humid and arid conditions were rarely seen. In the regional drought analysis using L-moment techniques with the SPEI values obtained, a region of five sites were accepted and the discordancy and heterogeneity measures showed that the basin was acceptable homogeneous. SPEI values are generally the best fit generalized extreme values (GEV) for 1 and 3-month periods, generalized normal (GNO) for 6-month period, generalized logistics (GLO) for 9-month period, Pearson type 3 (PE3) distributions for 12-month period. According to the regional SPEI values for reference periods, it has been found near-normal in 1.11, 1.25 and 2 years, moderately humid in 1.04 years, very humid conditions for 1.01 and 1.02 years, moderately dry in 4 and 5 years, severe arid in 10 years, and extremely dry conditions in 20 and longer periods.